Qushi Huayu decoction ameliorates non-alcoholic fatty liver disease in rats by modulating gut microbiota and serum lipids - Ni, Yiming; Wang, Xin; Wu, Qian; Yao, Yichen; Xu, Yuan; Li, Yuanyuan; Feng, Qin; Zhou, Mingmei; Gou, Xiaojun (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a multifactorial disease. As a clinical empirical prescription of traditional Chinese medicine, Qushi Huayu decoction (QHD) has attracted considerable attention for its advantages in multi-target treatment of NAFLD. However, the intervention mechanism of QHD on abnormal lipid levels and gut microbiota in NAFLD has not been reported. Therefore, we verified the therapeutic effect of QHD on high-fat diet (HFD)induced NAFLD in rats by physiological parameters and histopathological examination. In addition, studies on gut microbiota and serum lipidomics based on 16S rRNA sequencing and ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS) were conducted to elucidate the therapeutic mechanism of NAFLD in QHD. The changes in gut microbiota in NAFLD rats are mainly reflected in their diversity and composition, while QHD treated rats restored these changes. The genera Blautia, Lactobacillus, Allobaculum, Lachnoclostridium and Bacteroides were predominant in the NAFLD group, whereas, Turicibacter, Blautia, Sporosarcina, Romboutsia, Clostridium_sensu_stricto_1, Allobaculum, and Psychrobacter were predominant in the NAFLD+QHD group. Lipid subclasses, including diacylglycerol (DG), triglycerides (TG), phosphatidylethanolamine (PE), phosphatidylcholine (PC), phosphatidic acid (PA), phosphatidylserine (PS), lysophosphatidylinositol (LPI), and phosphatidylglycerol (PG), were significantly different between the NAFLD and the control groups, while QHD treatment significantly altered the levels of DG, TG, PA, lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), and platelet activating factor (PAF). Finally, Spearman's correlation analysis showed that NAFLD related differential lipid molecules were mainly associated with the genera of Bacteroides, Blautia, Lachnoclostridium, Clostridium_sensu_stricto_1, and Turicibacter, which were also significantly correlated with the biological parameters of NAFLD. Taken together, QHD may exert beneficial effects by regulating the gut microbiota and thus intervening in serum lipids.